Contribution of Teacher Competence (Pedagogy And Personality) In Teaching Practice During The Covid-19 Pandemic and 4.0 Era - Wardoyo, Cipto; Firmansyah, Rizky; Sunaryanto; Ma’ruf Nuris, Dudung; Galih Satriyo Wicaksono, Mochammad (Technium Social Sciences Journal, 2020)
The purpose of this study is to describe the role of accounting teachers during the Covid-19 pandemic and the 4.0 era by implementing pedagogic and personality competencies to build an appropriate online learning atmosphere for students. In a situation that does not provide certainty, the world of education must be more resilient and prepare all learning needs in any condition. The role of teachers in difficult times like this is very much needed, so that the aspect of teacher readiness is a major factor in the success of a lesson. In this study using a phenomenological approach. Data were collected through interviews that were set online. Qualitative data analysis was carried out in stages: Data Reduction, Data Presentation, Conclusion Drawing and Verification. The results of the study show that the contribution of pedagogic competence and personality helps teachers to shape student attitudes and behavior in online learning. Competence pedagogic help teachers to decide strategies and teaching methods that will be implemented, knowing the characteristics of learners, helped draft the learning and use the profit to evaluate learning activities that teachers can assess online learning which based on the needs of their students. Meanwhile, personality competence is a natural competence that is inherent in a teacher so that the attitudes and actions shown by the teacher are always the attention of students to be imitated and followed.